Typological features of the nervous system of cows depending on the reactivity and stress resistance - Karlova, L. V; Karlova, L.; Karlova, Lina V.; Karlova, Lina Valentinovna; Karlova, Lina Valentunivna; Karlova, Lina; Карлова, Ліна Валентинівна; Gavrilina, O.; Gavrilina, O. G.; Gavrylina, O.; Gavrylina, O. G.; Havrylina, O.; et al. (Alex Matsyura Press, 2018)
The article analyzes of stimulus of the central nervous system of Ukrainian red dairy cows, depending on the typological features of their higher nervous activity. The type of higher nervous activity was determined by the reaction of stimulation and inhibition using 20 % sodium bicarbonate solution of caffeine and conditional stimuli: sound (bell, tone high, tone low) and light (light white, light blue). The expediency of using a caffeine test for objective and more precision characterization of individual properties and typological features of the nervous system of cattle has been established. The dose of caffeine for cows with a strong, balanced, mobile type of nervous system was the highest – 1.08 ± 0.04 cm3 (P < 0.05). In cows with a weak type of higher nervous activity, the transcendens dose of caffeine is 0.45 ± 0.03 cm3, which causes inhibition, weakness, inertia and inequality of the nervous processes. Animals of the weak type have significantly lower initial excitability, are least reactive to the activating factors, form a conditional positive and negative connections with a higher load, the strength of which is low. The consequence of this is the slight restraint of the system of conditionally and unconditionally reflexes. Accordingly we investigat the lactic productivity of animals for I-III lactation using data from zootechnical records. The obtained data testify to the unequal adaptive capacity of cows of different types of nervous activity to external conditions. In cows of high types of higher nervous activity, unlike animals of the weak type, the level of milk production processes is higher, which confirms daily milk yield at a high percentage of dry substance and fat content in milk. It was established that the properties of cows nervous processes more influence on the milk indices (33.01 %; P < 0.01) and milk fat (16.01 %; P < 0.05) and less on the fat content of milk (2.34 %) On the basis of conducted complex studies was proved, the advantage of using animals of a strong, balanced, mobile type of the nervous system, which allows not only to increase milk productivity, but also to improve the component composition of milk. Викладено результати досліджень дії подразників на центральну нервову систему корів української червоної молочної породи залежно від типологічних особливостей їх вищої нервової діяльності. Тип вищої нервової діяльності визначали за реакцією збудження та гальмування з використанням 20 % розчину натрієво-бензойної солі кофеїну та умовних подразників: звукових (дзвінок, тон високий, тон низький) та світлових (світло біле, світло синє). Встановили доцільність використання кофеїнового тесту для об’єктивної та більш точної характеристики індивідуальних властивостей і типологічних особливостей нервової системи великої рогатої худоби. Доза кофеїну для корів з сильним урівноваженим рухливим типом нервової системи була найвищою – 1,08 ± 0,04 см3 (Р < 0,05). У корів зі слабким типом вищої нервової діяльності доза кофеїну 0,45 ± 0,03 см3 виявилась позамежною та проявилась гальмуванням, слабкістю, інертністю та неврівноваженістю нервових процесів. Тварини слабкого типу мали значно нижчу базову збудливість, проявляли найменшу реактивність до активуючих факторів та з більшим навантаженням формували умовні позитивні й негативні зв'язки, міцність яких була невисока. Наслідком цього встановлено легке гальмування системи умовно-безумовних рефлексів. Відповідно досліджували молочну продуктивність тварин за І-ІІІ лактації з використанням даних зоотехнічного обліку. Отримані дані свідчать про неоднакову пристосувальну здатність корів різних типів нервової діяльності до зовнішніх умов. У корів сильних типів вищої нервової діяльності, на відміну від тварин слабкого типу, рівень процесів молокоутворення вищий, що підтверджують добові надої при високій масовій частці сухої речовини та вмісту жиру в молоці. Встановлено, що властивості нервових процесів корів більше впливають на показники надою (33,01 %; Р < 0,01) та кількість молочного жиру (16,01 %; Р < 0,05) і менше на вміст жиру в молоці (2,34 %). На основі проведених комплексних досліджень доведена перевага використання тварин сильного урівноваженого рухливого типу нервової системи, що дозволяє не тільки підвищити молочну продуктивність, але й поліпшити компонентний склад молока.
Типологічні особливості нервової системи корів залежно від реактивності та стресостійкості організму
Карлова Ліна Валентинівна https://orcid.org/0000-0001-8213-8588 Гавриліна Олена Геннадіївна http://orcid.org/0000-0001-9624-9510 Алексєєва Наталія Вікторівна https://orcid.org/0000-0003-1984-5209
Keywords: dairy cattle breeding; молочне скотарство; types of higher nervous activity; типи вищої нервової діяльності; reactivity; реактивність; excitation and inhibition of nerve processes; збудження та гальмування нервових процесів; cattle; велика рогата худоба